The Performance of Competitiveness of Sharia Banking (Indonesia-Pakistan) Using Porter's Diamond Theory - Abdul Kadir Arno; Ishak Ishak; Fasiha Kamal (IAIN Padangsidimpuan, 2021)
This article provides an overview of the condition of the competitiveness of Islamic banking performance in Indonesia and Pakistan using the porter's diamond theory descriptive analysis method, namely (i) resource variables with indicators of Institutional Performance and Financial Performance, (ii) Demand Variables with Market share and financing indicators (iii) Industry variables related to indicators of the number of sharia business units, (iv) Strategy variables with the roadmap for the development of sharia banking. The conclusions in this study are: 1) The competitive advantages of Islamic banking in Indonesia in 2016-2020 namely Institutional Performance of Islamic commercial banks, average profit growth and average growth of third party funds, compared with the same indicators on Islamic banking in Pakistan. 2) Competitiveness of Islamic banking in Pakistan in 2016-2020, namely the Financial Ratio of NPF, FDR and BOPO which ranked first in terms of bank health level, and the average market share growth andfinancing growth compared to the same indicators in Islamic banking in Indonesia.Keywords: Islamic Banking Performance, Competitiveness, Diamond Porter theory.